The Role of Green Human Capital as a Mediation Variable Based on Improved Talent Management in Enhancing Green Innovation and En-vironmental Performance - Andap Budhi Revianto (International Business and Accounting Research Journal, 2023)
This study aims to analyze the role of green human capital as a mediating variable in increasing green innovation and environmental performance. The focus of this study was drawn to UMKM with a business oriented on the food industry. 200 UMKM in total were sampled for this study. In a subsequent phase, the researcher contacted the owners of 200 UMKM, and they were given a questionnaire to complete. Green transformational leadership and Green human resource management were the two independent variables that comprise the five variables used in this study and green human capital became mediating factor. Green innovation and environmental performance were two dependent variables. Data analysis in this study used SEM (Structural Equation Modeling). The research findings demonstrate that green transformational leadership has a positive and significant effect on green innovation. Green human resource management has a positive and insignificant effect on environmental performance. Green transformational leadership has a positive and significant effect on green human capital. Green human resource management has a positive and significant effect on green human capital. Green human capital has a positive and significant effect on green innovation. Green human capital has a positive and significant effect on environmental performance. This study is limited by the fact that it only collected information from specialized culinary UMKM. Therefore, the following study can broaden the subject of study to include other aspects of UMKM outside culinary.